HLA and Associated Important Diseases - Xi, Yongzhi (IntechOpen, 2014)
This year marks the 60th anniversary of HLA discovery by the French Nobel laureate physician Jean Dausset, as well as the 55th anniversary of the identification and naming of the first HLA. Under such circumstances, both basic HLA research and its clinical applications need a new book that comprehensively reflects the latest achievements in the field. Thus, Professor Xi as Editor has contributed to organize international experts in the areas of HLA-related basic research and clinical applications, to unite their knowledge in chapters covering various related topics, and finally to finish the book "HLA and Associated Important Diseases". The book consists of three sections which mainly include basic theoretical and technological developments, several important HLA-associated autoimmune diseases and HLA-associated infectious diseases.